2021
DOI: 10.30574/wjarr.2021.9.3.0075
|View full text |Cite
|
Sign up to set email alerts
|

Catalogue of Some Saltwater and Freshwater Fish Species of the Niger Delta Region of Nigeria

Abstract: The study was done to review some saltwater and freshwater fish species in the Niger Delta region of Nigeria. The Niger Delta is one of the most prominent regions in Nigeria, endowed with several water bodies that are distributed as freshwater like rivers, lakes, streams and creeks. These freshwater ecosystems in the region, are abundantly endowed with fish species such as Clarias gariepinus, Pila ovate, Labeo coubie, Synodontis budgetti and Synodontis eupterus. Apart from the freshwaters, the region also has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Ekinadose et al (2021) [16] who worked at East coast of North America from Cape Breton, St John's River in Florida and reported that plankton, small fishes, shrimp were the main food items of A. aestivalis. Zooplankton play an important role in nutrient cycling in aquatic ecosystems and support healthy fish population (Lampart and Sommer, 2007) [30] .…”
Section: Discussion 41 Food Items and Feeding Habit Of Alosa Aestivalismentioning
confidence: 99%
“…Ekinadose et al (2021) [16] who worked at East coast of North America from Cape Breton, St John's River in Florida and reported that plankton, small fishes, shrimp were the main food items of A. aestivalis. Zooplankton play an important role in nutrient cycling in aquatic ecosystems and support healthy fish population (Lampart and Sommer, 2007) [30] .…”
Section: Discussion 41 Food Items and Feeding Habit Of Alosa Aestivalismentioning
confidence: 99%
“…9 Tilapia guineensis, commonly known as the Guinean tilapia, is a widely distributed freshwater fish species found in various aquatic habitats. 10,11 Due to its ecological and economic importance, it serves as an excellent indicator species for assessing the impact of environmental contaminants on aquatic ecosystems. 12 As emulsifiers can be discharged into aquatic environments through industrial effluents or accidental spills, understanding their effects on T. guineensis is essential for evaluating potential risks and implementing effective mitigation measures.…”
Section: Introductionmentioning
confidence: 99%